2007
DOI: 10.1016/j.worlddev.2006.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Fear of China: Is There a Future for Manufacturing in Latin America?

Abstract: The Inter-American Development Bank (IADB), through the Integration and Regional Programs Department, and the Asian Development Bank (ADB), through the ADB Institute jointly coordinate the "Latin America/Caribbean and Asia/Pacific Economics and Business Association (LAEBA)." LAEBA is dedicated to advancing economic linkages between the two regions through cross-regional and comparative research and exchange. The LAEBA initiative results from an inter-agency Partnership Agreement signed on March 17th, 2001 betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(47 citation statements)
references
References 19 publications
1
41
0
5
Order By: Relevance
“…They have used various methods, including inspection of trade data (e.g. Lall et al 2005;Mesquita Moreira, 2007;Kaplinsky and Morris, 2008), revealed comparative advantage calculations (Lederman et al, 2008), gravity models (e.g. Greenaway et al, 2008;Hanson and Robertson, 2010) and computable general equilibrium (CGE) models (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…They have used various methods, including inspection of trade data (e.g. Lall et al 2005;Mesquita Moreira, 2007;Kaplinsky and Morris, 2008), revealed comparative advantage calculations (Lederman et al, 2008), gravity models (e.g. Greenaway et al, 2008;Hanson and Robertson, 2010) and computable general equilibrium (CGE) models (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…One of these is Mexico's institutional weakness vis‐à‐vis deepened reliance on TNCs and FDI in export‐led development. Another factor is the change of the global system of production in which nation states, such as those in Asia, have strategically leveraged their industries to take advantage of global value‐chain restructuring (Mesquita Moreira, 2007), while TNCs have taken advantage of their freedom to relocate activities regionally and internationally. Jessop and Sum (2000) contrast this glocalization process with strategic ‘glurbanization’, a process whereby cities enhance their place‐based competitive advantage in the world economy to procure and retain FDI.…”
Section: Resultsmentioning
confidence: 99%
“…This failure of central planning was evident in all countries that we now know as the BRIIC group of emerging economies. In Latin America import substitution strategies failed and fossilized industries that were protected from (international) competition lost market shares both at home and abroad (Taylor, 1998, Mesquita Moreiraa 2007. The leap-forward strategy that had prioritized heavy industry had completely failed to deliver the desired catching up with the industrialized economies, not only in the major communist economies (China and the former USSR), but also in India and other noncommunist countries (Lin, 2009).…”
mentioning
confidence: 99%